2002
DOI: 10.1094/pdis.2002.86.9.955
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Disease in Fresh-Market Tomato Grown in Differing Bed Strategies and Fungicide Spray Programs

Abstract: A 3-year field study in central Maryland evaluated foliar disease in fresh-market tomato grown using combinations of four bed strategies and three fungicide programs. Bed strategies included uncovered beds with or without a composted dairy manure amendment or beds covered with black polyethylene or hairy vetch mulch. Fungicide programs included no fungicide, weekly fungicide, or fungicide applications scheduled according to the TOMCAST disease predictor. In plots with hairy vetch-covered beds, early blight cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…As a compromise, it has also been shown that long-term strip tillage made a more hospitable environment for earthworm growth and reproduction in comparison with conventional full-width tillage (Overstreet et al 2010). From a productivity perspective, similar yields in no-tillage and tilled vegetable crops were reported when cover-crop regrowth did not occur and adequate irrigation was provided (Teasdale and Abdul-Baki 1995;Abdul-Baki et al 1996;Creamer et al 1996;Mills et al 2002;Madden et al 2004). For example, a no-tillage roller/crimper system using rye-hairy vetch or wheat-winter pea covers for an irrigated organic tomato crop was found to provide results for plant growth, number of fruits, and yield similar to those achieved in a tilled system (Delate et al 2012).…”
Section: B Soil Healthmentioning
confidence: 99%
“…As a compromise, it has also been shown that long-term strip tillage made a more hospitable environment for earthworm growth and reproduction in comparison with conventional full-width tillage (Overstreet et al 2010). From a productivity perspective, similar yields in no-tillage and tilled vegetable crops were reported when cover-crop regrowth did not occur and adequate irrigation was provided (Teasdale and Abdul-Baki 1995;Abdul-Baki et al 1996;Creamer et al 1996;Mills et al 2002;Madden et al 2004). For example, a no-tillage roller/crimper system using rye-hairy vetch or wheat-winter pea covers for an irrigated organic tomato crop was found to provide results for plant growth, number of fruits, and yield similar to those achieved in a tilled system (Delate et al 2012).…”
Section: B Soil Healthmentioning
confidence: 99%
“…Up-regulated genes included the most abundant chloroplast protein, ribulose bisphosphate carboxylase/oxygenase (Rubisco), important for carbon fixation; nitrogen-responsive glutamine synthase, regulating carbon/nitrogen signaling; nitrogen utilizing and nitrite toxicity reducing nitrite reductase; nitrogen-use efficiency protein glucose-6-phosphate dehydrogenase; chaperone proteins (HSP70 and ER protein BiP) that stabilize native proteins; cytokinin-and gibberellin-related regulatory proteins; and plant defense anti-fungal proteins chitinase and osmotin. Up-regulation of these plant defense genes may contribute to disease resistance as, in these and other field experiments, hairy vetch-grown tomato had less disease than tomato grown under black plastic [52,53,55].…”
Section: Impact Of Hairy Vetch Cropping System On Tomato Physiologymentioning
confidence: 72%
“…It was thought that more complete coverage of the soil surface with the hairy vetch mulch (hairy vetch mulch covers the entire field while black plastic covers the tomato beds but not the interspaced rows) physically obstructed splashed soil near the soil surface preventing soil infested with pathogen inoculum from entering the tomato canopy. The tomato crop grown in the hairy vetch mulch had negligible loss to early blight in the absence of fungicide relative to the fungicide treated controls [52,53]. There was also greater resistance of the tomato crop grown in the hairy vetch mulch to invasion and damage by the Colorado potato beetle [54].…”
Section: Next-generation Cover Crop-based Sustainable Tomato Productimentioning
confidence: 95%
See 1 more Smart Citation
“…In conventional production systems, tomato early blight is almost exclusively managed by intensive fungicide spray programmes with or without a disease forecasting system (Madden et al 1978;Brammall 1993;Keinath et al 1996;Dillard et al 1997;Mills et al 2002;Cowgill et al 2005). Several effective fungicides have been registered for use against this disease on several hosts (Bartlett et al 2002).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%